Heaviness in Metal Music Production, Volume I: How and Why It Works - Herbst, Jan-Peter; Mynett, Mark (Routledge, 2026)
Heaviness in Metal Music Production, Volume I: How and Why It Works provides an in-depth analysis of the art and craft of producing heaviness, the fundamental musical quality in metal music. Using primarily ethnographic research which draws on interviews and engineering documentation from various producers across different generations, the distinguishing feature of the study is the song 'In Solitude', which was written, recorded, and produced by the researchers themselves. Written by practising musicians, producers, and experts in music technology and musicology, this book offers a comprehensive understanding of the interplay between structural, performative, and technological components of a metal recording; the perceptual and discursive factors determining heaviness; and the relationship between creative freedom and technical demands in contemporary metal music production. Heaviness in Metal Music Production is a rigorous academic study that advances the field of metal music production research through an innovative and methodologically robust approach. At its core is an unprecedented experiment in which eight leading producers each mixed the same song, with their processes meticulously documented and analysed through in-depth interviews. This study not only provides unique insights into the conceptualizations and craft of heaviness in metal music production but also sets a new standard for empirical research in the discipline. As a result, it serves as a vital resource for scholars, researchers, and students in audio engineering and metal music studies, making it essential supplementary reading for advanced undergraduates, postgraduates, and academics engaged in these fields. This two-volume set offers a well-rounded insight into the production of heaviness in theory and practice.